Constantin Brâncoveanu (1654 – 1714) (Confluenţe Bibliologice, 2024)
The article reviews the essential data related to the activity of Constantin Brâncoveanu, who was the ruler of Wallachia between 1688 and 1714, having one of the longest reigns in the history of the Romanian Principalities. Several topics related to Constantin Brâncoveanu’s concerns are addressed: the socio-economic situation in the country, culture, Brâncoveanu’s foreign policy and the tragic end of the ruler.
Keywords: historical personality; Romanian history